Mass transfer modeling during osmotic dehydration of Chub Mackerel (Scomber Japonicus) slices in salt and glycerol solution at different temperatures - Checmarev, Gerardo (2014)
The use of osmotic dehydration to preserve fish products could be an interesting option in order to maintain the characteristics of food. The objective of this research was to study the mathematical modeling of water loss and solute gain during the cooking-infusion of chub mackerel (Scomber japonicus) slices at different temperatures. Osmotic dehydration was performed by cooking-infusion in solutions containing 54% (w/w) glycerol and 7% (w/w) salt (solution aw = 0.64) at different temperatures (50, 70 and 90C). Experimental results were adjusted to the Crank, Weibull, and Zugarramurdi & Lupín models. Mass transfer kinetics of water, salt and glycerol during osmotic dehydration of chub mackerel slices were adequately adjusted, with similar accuracy, by the three models. However, the Zugarramurdi & Lupín model was preferred because it also allowed the prediction of water and solids contents at equilibrium, which is relevant for the development of this kind of products.